Evaluation of Yausa as a Natural Coagulant in the treatment of waters for human consumption - Delgado Garcés, Sebastián; Benavides Revelo, María Camila; Gordillo Plata, Lucia (Boletín Informativo CEI, 2019)
Water in its natural state has characteristics that can be harmful to humans; one of the most relevant are turbidity and color, which are mainly caused by very small particles. These micro particles remain suspended in the water for a long time; for their elimination the coagulation process is used. Currently, to carry out the coagulation process, chemical coagulants such as aluminum sulfate, ferric chloride and aluminum polychloride are commonly used; its use can present disadvantages in the short and long term; for this reason is intended to determine by means of laboratory tests, the properties of the Yausa (Abutilon Insigne Planch) as coagulant, because it is a mucilaginous plant that has clarifying properties; this, in order to evaluate the substitution of chemicals in the water treatment process for human consumption, complying with Colombian regulations. For this research, factors such as pH, color, turbidity, alkalinity, the necessary coagulant dose and the optimal velocity gradient should be taken into account; the initial characteristics of the water to be treated and the final characteristics after the application of the coagulant.